AL-QUR’AN DAN BUDAYA ARAB KRITIK TERHADAP PEMIKIRAN NASR HAMID ABU ZAYD - dedi saripgani (STIU Al-Mujtama Pamekasan, 2019)
Abstract: As a thinker, Abu Zayd developed a hermeneutic theory which held that the Qur’an was a human text. According to him, the Qur’an uses cultural language and is formed in a particular cultural context, so that the Qur’an is a cultural product. In the perspective of 'Ulum al-Qura>n, Abu Zayd's thinking has come out from the footing of the scholars, starting from his erroneous historical analysis, his misunderstanding of the wisdom of the decline of the Qur’an, his misunderstanding of several concepts of the scholars in the problem of asba>b al-nuzu>l, and his rejection of history as a data source. Based on this problem, the following article will critically examine Abu Zayd's thoughts. The research method used in this study is library research, where the study is explained descriptively and critically. Then, the type of data used is literature literary data with two data sources, namely the primary source in the form of Abu Zayd's original work and secondary sources in the form of other works that are directly or indirectly related to research studies. The theoretical framework used in this study is a general religious discourse. The results of this study indicate that the concept of asba>b al-nuzu>l initiated by Abu Zayd focused on the problem of the relationship between text and reality. To elaborate on this conception, Abu Zayd detailed it in four basic problems, namely the reasons for the gradual decline of the Qur’an, the gradual model of decline, the concept of dalâlah in understanding a verse and its relation to asba>b al-nuzu>l and finally on how to determine asba>b al-nuzu>l. Keywords: Criticism,‘ulu>m al-Qur’a>n, asba>b al-nuzu>l, Abu Zayd.